(untitled) (Journal of Mechanical Engineering, 2019)
One set of Al–Mg and Al-Mg-Zr alloys are directly cold rolled and other set of those alloys are hot rolled and then cold rolled using a laboratory rolling mill. The effect of rolling on the fractional recrystallization of the alloys has been investigated using the micro-hardness variation. Isothermally annealed samples are also studied using JMAK type analysis to see if there exists any correlation between experimental and JMAK type analysis. From the microstructure, it is observed that the Al-Mg alloy becomes almost fully recrystallized state after annealing at 600°K for 60 minutes. The results also show that recrystallization fraction obtained by the two methods, shows the higher variation in zirconium added Al-Mg alloy as compared to the Al-Mg alloy. The fractional recrystallization of the cold rolled Al-Mg-Zr alloy is significantly lower than that of cold rolled Al-Mg alloy and hot and colled rolled Al-Mg-Zr, owing to the presence of fine Al3Zr precipitates. These metastable L12 Al3Zr precipitates are thermally stable at high annealing temperatures.